Multidisciplinary Assessment of 100 Athletes With Groin Pain Using the Doha Agreement: High Prevalence of Adductor-Related Groin Pain in Conjunction With Multiple Causes. Issue 4 (July 2018) - Taylor, Rachel; Vuckovic, Zarko; Mosler, Andrea; Agricola, Rintje; Otten, Roald; Jacobsen, Philipp; Holmich, Per; Weir, Adam
Abstract : Objective: To examine the prevalence of different causes of groin pain in athletes using the recent Doha consensus classification of terminology and definitions of groin pain in athletes. Design: Descriptive epidemiological study. Setting: Multidisciplinary sports groin pain clinic at Aspetar Orthopedic and Sports Medicine Hospital, Doha, Qatar. Patients: The clinical records of 100 consecutive athletes with complaints of groin pain who attended the multidisciplinary sports groin pain clinic between January and December 2014 were analyzed. Main Outcome Measures: The causes of groin pain were categorized according to terminology and definitions agreed upon at the Doha consensus meeting on groin pain classification in athletes. The classification system has 3 main subheadings; defined clinical entities for groin pain (adductor-related, iliopsoas-related, inguinal-related, and pubic-related groin pain), hip-related groin pain, and other causes of groin pain in athletes. Results: The majority of athletes were male (98%) soccer players (60%). Multiple causes for groin pain were found in 44% of the athletes. Adductor-related groin pain was the most prevalent defined clinical entity (61% of athletes), and pubic-related groin pain was the least prevalent (4% of athletes). Conclusions: Adductor-related groin pain is the most commonly occurring clinical entity in this athlete population in mainly kicking and change of direction sports and frequently, multiple causes are found. Clinical Relevance: This is the first study to use the Doha agreement classification system and highlights the prevalence of adductor-related groin pain and that often multiple clinical entities contribute to an athlete's groin pain. Consequently, prevention programs should be implemented with these factors in mind.